Pengaruh Good Corporate Governance Terhadap Konservatisme Akuntansi - Dyah Novitasari; Suwarno Suwarno (Journal of Culture Accounting and Auditing, 2022)
This study aims to empirically examine the effect of Good Corporate Governance on accounting conservatism. The population of this study is a publicly listed company on the Indonesia Stock Exchange(IDX) which is in the property and real estate sector in the period 2017-2019. The research sample was determined using the purposive sampling method which resulted in a research sample of 90 observations. The data analysis technique used in this research is multiple linear regression analysis. The test results show that the independent board of directors and commissioners have no effect on accounting conservatism. While the audit committee has a significant effect on accounting conservatism.